Routine activity theory and research ethics: a criminological approach - Pimple, Kenneth D., author (Colorado State University. Libraries, 2016)
Research misconduct is often attributed to pressure or bad apples. There is little use of these folk theories because all professional scientists in the United States are always under pressure and, apparently, bad apples are only discovered after misconduct has been committed. These theories do not offer any explanatory or predictive promise because they focus on the multifaceted individual within a multifaceted population. Until the late 20th century, efforts by criminologists trying to understand who become criminals focused on interior, individual qualities, such as temperament or faulty cognition. More recently, two closely related ways of understanding and preventing crime: the more abstract Routine Activity Theory (RAT) informing the more concrete Situational Crime Prevention (SCP). While research misconduct is not technically a crime, they are analogs, and the insights of criminology can fruitfully be applied to the practice of science. In short, we should pay attention to the ways day-to-day routines of doing science make it difficult or easy to commit research misconduct. If only one person – say a graduate student – ever saw raw data, the PI has little chance of recognizing falsification, and a PI who always or randomly scrutinizes raw data will naturally deter most would-be bad actors. In this talk, I will briefly explain RAT and SCP, provide additional examples from criminology and possibly useful examples for science.
Presented at the Retractions conference: keeping the pool clean: prevention and management of misconduct related retractions held on July 20-21, 2016 at Hilton Fort Collins in Fort Collins, Colorado.
Kenneth D. Pimple, Ph.D., is Associate Scholar at Indiana University Bloomington (IUB) and Affiliate Faculty of the Indiana University Center for Bioethics. He has twenty years-five years of experience in research, teaching, and service on practical and professional ethics with a concentration on research ethics. He is especially known for organizing faculty workshops on ethics and research ethics. His publications include two books and more than twenty invited or peer-reviewed papers in journals including Communications of the ACM, Journal of Medical Ethics, Accountability in Research, Science and Engineering Ethics, and others. His service activities have included membership on advisory boards for three projects funded by the National Science Foundation and one funded by the National Institutes of Health; the Data and Safety Monitoring Board for the Comprehensive Sickle Cell Centers of the National Heart, Lung, and Blood Institute, National Institutes of Health; Bloomington Hospital's Institutional Review Board (IRB); and a number of committees at Indiana University, including the Institutional Animal Care and Use Committee (IACUC); the Committee on Research Fraud and Misconduct; the Human Subjects Protection Education Committee; and the Human Subjects Committee (IRB).
PowerPoint presentation given on Day 1: Wednesday, July 20th, 2016.
Accessibility features: Transcript.
Keywords: routine activity theory (RAT); situational crime prevention (SCP); enforcement; power of situation; Plagiarism